2014
DOI: 10.1140/epjc/s10052-014-2935-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantum influence of topological defects in Gödel-type space-times

Abstract: In this contribution, some solutions of the Klein-Gordon equation in the Gödel-type metrics with an embedded cosmic string are considered. The quantum dynamics of a scalar particle in three spaces whose metric is described by different classes of Gödel solution, with a cosmic string passing through the spaces, is found. The energy levels and eigenfunctions of the Klein-Gordon operator are obtained. We show that these eigenvalues and eigenfunctions depend on the parameter characterizing the presence of a cosmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
105
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(126 citation statements)
references
References 48 publications
(50 reference statements)
16
105
1
4
Order By: Relevance
“…In the limit of = 0, a spectrum similar to the Landau levels is recovered. Note that this dynamics in the presence of the confining potential due to the Klein-Gordon oscillator reinforces the characteristics of the quantum dynamics observed in this Gödel-type spacetime [59][60][61], which are characterized by the similarity with the Landau problem for a charged particle on a surface exposed to a uniform magnetic field. Based on this analogy, Druker et al [59] have suggested the picture of a holographic description for a single chronologically safe region.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In the limit of = 0, a spectrum similar to the Landau levels is recovered. Note that this dynamics in the presence of the confining potential due to the Klein-Gordon oscillator reinforces the characteristics of the quantum dynamics observed in this Gödel-type spacetime [59][60][61], which are characterized by the similarity with the Landau problem for a charged particle on a surface exposed to a uniform magnetic field. Based on this analogy, Druker et al [59] have suggested the picture of a holographic description for a single chronologically safe region.…”
Section: Discussionsupporting
confidence: 76%
“…This is equivalent to the energy levels in the Gödel-type spacetimes studied by us [59][60][61]64]. Although Eq.…”
Section: Kg Oscillator In Cosmic Dislocation In Som-raychaudhuri Spacmentioning
confidence: 96%
See 1 more Smart Citation
“…A close relation was seen between a family of Gödel-type solutions of 3+1 general relativity and the Landau problem, as reported by Drukker [8]. The quantum dynamics of a scalar particle in three spaces whose metrics are described by different classes of Gödel solutions, with a cosmic string passing through the spaces has been studied [9]. The solutions of the Klein-Gordon equation in the background of KerrNewman, Gödel and Friedmann-Robertson-Walker spacetimes with a cosmic string passing through them have been obtained; some of their consequences have been discussed, with emphasis on the role played by the presence of the cosmic string [10].…”
Section: Introductionsupporting
confidence: 55%
“…In this case, we have the new coordinates R = i 2l and θ = r R [9]; then the line element (2.1) becomes…”
Section: Derivation Of Dkp Elements In the Presence Of Gödel-type Bacmentioning
confidence: 99%